2011
DOI: 10.1016/j.ausmj.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

“You Wouldn't Know it Had Alcohol in it until you Read the Can”: Adolescents and Alcohol-Energy Drinks

Abstract: Young Australians’ perceptions, and consumption, of alcohol-energy drinks were examined via a multi-method study conducted in late 2008. The study consisted of: 12 focus groups with 12- to 17-year-olds from metropolitan, regional and rural New South Wales ( n=95); and a survey of 12- to 17-year-olds with data collected through schools, intercepts, and the Internet ( n=1263). Alcohol-energy drinks were a popular product among adolescent participants, with similarity to soft drinks identified as a primary appeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Typical responses included: “Wakes you up, makes you feel alert and it tastes nice”; “It makes me go hyper” and “I drink it before soccer and I don't lose energy as fast”. 72 Jones 71 explored perceptions of alcohol-energy drinks (AEDs) among 12–17 years and suggested that young people liked them because they increased the ‘fun’ at parties and acted as a ‘pick me up’. They also found that the packaging of AEDs (to look like soft drinks) was a factor, particularly for younger teenagers and girls.…”
Section: Resultsmentioning
confidence: 99%
“…Typical responses included: “Wakes you up, makes you feel alert and it tastes nice”; “It makes me go hyper” and “I drink it before soccer and I don't lose energy as fast”. 72 Jones 71 explored perceptions of alcohol-energy drinks (AEDs) among 12–17 years and suggested that young people liked them because they increased the ‘fun’ at parties and acted as a ‘pick me up’. They also found that the packaging of AEDs (to look like soft drinks) was a factor, particularly for younger teenagers and girls.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that AEDs may facilitate alcohol consumption because the caffeine in energy drinks reduces sedation and increases stimulation, thereby masking signs of intoxication (meaning the drinker is more likely to be involved in risk‐taking activities) 10 . Given the clever and appealing marketing of AEDs towards young people and their sweet, palatable taste, 22,23 it is not surprising to find such high levels of use at schoolies. However, AED use may have been elevated by the presence of a Red Bull promotional team at the Lorne site offering free Red Bull cans to schoolies.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the maximum concentration of caffeine and restricting the range of foodstuffs that may contain added caffeine would reduce the frequency of caffeine dependence in the population, including in children. Packaging should aim to more clearly and comprehensibly inform consumers as to which products are highly caffeinated or have alcohol, 34 as well as their nutritional content – especially important for ‘non‐traditional’ highly caffeinated foodstuffs. Maximum daily use recommendations on packaging need to harmonise those due to caffeine with those due to any alcohol component.…”
Section: Risk Mitigation – Possible Policy Responsesmentioning
confidence: 99%
“…Packaging should aim to more clearly and comprehensibly inform consumers as to which products are highly caffeinated or have alcohol, 34 as well as their nutritional content -especially important for 'non-traditional' highly caffeinated foodstuffs. Maximum daily use recommendations on packaging need to harmonise those due to caffeine with those due to any alcohol component.…”
Section: Risk Mitigation -Possible Policy Responsesmentioning
confidence: 99%